(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Traditional education is our primitive technique of instruction, as is both the current education system and the new method of instruction. Between the current educational system and the primitive educational system, there is a lot of misunderstanding. Computers and the internet are essential tools in modern schooling. In the minds of students who are deciding whether to pursue online or traditional education, sitting in front of a computer or sitting in a classroom is the obvious distinction. Aside from the difference in learning styles, technology, and the learning environment, there is also a distinction between online and conventional schooling. In this paper discuss the traditional and modern education system and its methods and technique, difference between traditional and modern education system.